Mesenchymal stem cells-macrophages crosstalk and myeloid malignancy - Li, Kun; Nie, Hongyan; Jin, Runming; Wu, Xiaoyan (Frontiers in Immunology, 2024)
As major components of the tumor microenvironment, both mesenchymal stem cells (MSCs) and macrophages can be remodelled and exhibit different phenotypes and functions during tumor initiation and progression. In recent years, increasing evidence has shown that tumor-associated macrophages (TAMs) play a crucial role in the growth, metastasis, and chemotherapy resistance of hematological malignancies, and are associated with poor prognosis. Consequently, TAMs have emerged as promising therapeutic targets. Notably, MSCs exert a profound influence on modulating immune cell functions such as macrophages and granulocytes, thereby playing a crucial role in shaping the immunosuppressive microenvironment surrounding tumors. However, in hematological malignancies, the cellular and molecular mechanisms underlying the interaction between MSCs and macrophages have not been clearly elucidated. In this review, we provide an overview of the role of TAMs in various common hematological malignancies, and discuss the latest advances in understanding the interaction between MSCs and macrophages in disease progression. Additionally, potential therapeutic approaches targeting this relationship are outlined.